Smart In-Car Speed Monitoring System, The Effect of Grace Period on Driving Behavior - M. Zaidan, Hakam; Al Rozz, Younis; Alhelal, Dheyaa; Mohammed, Emad Ahmed; Mujhid, Ibrahim Jameel (Journal of Soft Computing and Data Mining, 2026)
High and excessive speed is one of the leading causes of traffic accidents, leading to fatalities and serious injuries worldwide. In Iraq, there was a 21% increase in casualties by 2017. This study presents a speed monitoring system in which the driver gets alerted by an audible alarm in case of over-speeding. A grace period of 10 seconds is allowed so that the driver tries to reduce the car’s speed. A ticket is issued via SMS message if the driver fails to decelerate within that period. Thus, prioritizing safety awareness over immediate punitive measures. The system was tested through 40 car trips, carried out by four drivers, 20 trips without an alarm and 20 with an alarm. Multiple statistical tests were used to evaluate the system. Results revealed that incorporating the alarm achieved a reduction of 21%, with *p*=.039 in speed mean, and 14% with *p*=.002 in speed variability. Additionally, tickets were decreased by 89% with high statistical significance (?p? < .001). Furthermore, statistically, trips with an alarm revealed 84% lower odds of receiving a ticket in comparison with the trips without an alarm. On the other hand, results showed that there is no correlation between temperature and speeding (p > .05, indicating that there is no statistical significance).